Have Guidelines About Smoking Cessation Support in Pregnancy Changed Practice in Victoria, Australia?. Issue 2 (25th March 2013) - Perlen, Susan; Brown, Stephanie J.; Yelland, Jane
Abstract Background Antenatal smoking cessation guidelines have been available in Victoria, Australia, for the past decade. The objective of this study was to assess to what extent introduction of smoking cessation guidelines in pregnancy changed practice in Victorian public hospitals. Methods Two population‐based postal surveys of women giving birth in the state of Victoria, conducted in 2000 and 2008 before and after implementation of smoking cessation guidelines. Self‐administered questionnaires were distributed by hospitals and home birth practitioners to women 5–6 months postpartum. Results Surveys were completed and returned by 67 percent of eligible women (1, 616/2, 412) in 2000 and 51% (2, 900/5, 681) in 2008. Compared with the 2000 survey, women in the 2008 survey attending public sector care were more likely: to receive advice on how to stop smoking (Adjusted Odds Ratio: 2.2, 95% CI 1.5–3.2); to be given written information (Adj OR: 2.7, 95% CI 1.8–4.0); to be referred to stop smoking programs (Adj OR: 6.1, 95% CI 3.1–11.7); and to have discussed smoking cessation at more than one visit (Adj OR: 1.5, 95% CI 1.0–2.2). While the majority of women in both surveys were asked about smoking in early pregnancy, about half of those smoking did not receive advice on how to stop or cut down; were not given written information; were not told about/referred to stop smoking programs and were not asked again about smoking at subsequent visits. The significant shift in women's reports of receiving smoking cessation advice and support between the two surveys occurred predominantly at public hospitals where women received all or some antenatal care. Conclusions Smoking cessation guidelines in Victorian public hospitals have increased the extent to which pregnant women receive advice and support to stop or reduce smoking. However, half of smokers did not receive the full complement of advice and support according to state guidelines, with marked variability according to where and from whom women received antenatal care. Further efforts are needed to implement smoking cessation advice and support in clinical practice.